Analisa Lembaran Komposit Berpenguat Serbuk Ijuk Mesh 40 Menggunakan Matrik Karet Alam Dengan Variasi Komposisi Serbuk Ijuk 0 PHR, 10 PHR, 20 PHR Terhadap Daya Serap Radiasi Sinar Gamma - Wibowo, Arif Adi, Ir. Masyrukan, MT, Tri Widodo B. R., ST., Msc., PhD (2016)
The purpose of this study is to determine how much gamma ray radiation absorption of the composite particles of 40 mesh fibers with a rubber matrix. Composite manufacturing process begins with the preparation of materials to be used, namely: palm fiber, latex I radiation 60%, ZnO, ZDEC, Ionol, sulfur. Fibers are used as filler, originally from the fibers, the fibers are made into powder without treatment (treatment) that could change the nature ijuknya own. Compound made there are 3 variations for comparison. What distinguishes the particle composition fibers, fibers 0 PHR, fibers 10 PHR and 20 PHR fibers. In the manufacture of compounds, chemicals used previously done dispersion in advance so that the chemicals are homogeneous. Dispersion is carried out 24 hours and 48 hours to sulfur. Mixing of composite materials made on a glass and stirred for 15 minutes then pour in the mold with the dimensions specified. The next process of vulcanization by using an oven and heated at a temperature of 90o within 1 hour. The test results can be concluded that the higher the content of particles fibers, the higher also the value of the power absorbed. Keywords: Fibers, Latex I radiation 60%, variation of composition, gamma rays